Fabrication of Co doped MoS2 nanosheets with enlarged interlayer spacing as efficient and pH-Universal bifunctional electrocatalyst for overall water splitting. Issue 17 (1st September 2021) - Wei, Qinghe; Wang, Dan; Zhang, Lili; Zhao, Liqing; Zhang, Bing; Zhou, Guoli; Zhao, Yafei
Abstract: Exploring inexpensive and active bifunctional electrocatalysts to produce hydrogen and oxygen from water at all pHs is highly desirable. Herein, we report a facile one-step method to prepare vertically aligned Co doped MoS2 nanosheets with extended interlayer distance on carbon cloth (Co–MoS2 @CC) for full hydrolysis in both alkaline and acidic medium. Co–MoS2 @CC exhibits long-term durability with overpotentials of 56.6 mV and 130 mV for hydrogen generation and 242 mV and 201 mV for oxygen production at 10 mA cm −2 in basic and acidic conditions, respectively. Moreover, we achieve low voltages of 1.585 V and 1.55 V in basic and acidic conditions respectively for the overall water splitting. We assume that such excellent property of Co–MoS2 @CC may be ascribed to the uncovering of more active sites and high porosity resulted from Co doping, which boosts the conductivity and thus reduces MoS2 hydrogen adsorption free energy in HER, as well as benefits to catalytic active sites in OER. This one-step doping approach opens up new ways to regulate the intrinsic catalytic activity to catalyze total hydrolysis at all PHs.